Professional Zakat as a Catalyst for Welfare: Strategic Mapping for Sustainable Economic Growth in Semarang - Ishmah Afiyah; M Mahmudulhassan (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the role of professional zakat in improving the economic welfare of people in the Semarang and to identify optimal mapping strategies for sustainable economic growth in the region. A qualitative approach was used in this study, using in-depth interview techniques and documentation analysis. Primary data was collected from respondents consisting of zakat practitioners, beneficiaries, and related stakeholders in Semarang. In addition, secondary data from related literature and official government documents were also analyzed to support the research findings. The results showed that professional zakat has great potential as a catalyst to improve the economic welfare of people in Semarang. Optimal mapping strategies include identifying economic sectors in need of assistance, developing training and mentoring programs, and establishing strategic partnerships between zakat organizations, governments, and the private sector. This mapping provides a strong foundation for sustainable economic growth by ensuring the effective and efficient distribution of zakat and strengthening the economic capacity of local communities. This research provides valuable insights for policymakers, zakat practitioners, and other stakeholders to develop more effective strategies in utilizing professional zakat as an instrument to improve the economic welfare of the community and promote sustainable economic growth in the Semarang.